Navigating the future: exploring technological advancements and emerging trends in the sustainable ornamental industry - Wani, Muneeb Ahmad; Din, Ambreena; Nazki, Imtiyaz Tahir; Rehman, Tanzeel U.; Al-Khayri, Jameel M.; Jain, Shri Mohan; Lone, Raiz Ahmed; Bhat, Zahoor Ahmad; Mushtaq, Muntazir (Frontiers in Environmental Science, 2023)
Technological advances have played a critical role in the production of flower crops, enabling farmers to maximize yields and reduce losses while also improving the quality of flowers. These advances have included the development of new breeding techniques, such as molecular marker-assisted breeding, and the use of modern technologies like high-throughput phenotyping to identify and select superior cultivars. In addition, precision farming techniques, such as the use of sensors and remote monitoring systems, have made it possible to closely monitor crop growth and optimize inputs like water and fertilizer, leading to higher yields and improved resource efficiency. Advancements in biotechnology have also resulted in the development of transgenic plants that are resistant to pests and diseases, reducing the need for chemical pesticides and improving plant health. Modern molecular genetic tools, particularly genome editing with CRISPR/Cas9 nucleases, are emerging in addition to conventional approaches of to investigating these plants. Furthermore, the use of novel growing systems, such as hydroponics and vertical farming, has allowed for year-round flower production in controlled environments, mitigating the challenges associated with seasonal changes and climate variability. These innovations have also made it possible to produce high-quality flowers in urban areas, bringing fresh blooms closer to consumers. Overall, technological advances in flower crops have revolutionized the floriculture industry, enabling growers to produce high-quality flowers in a more sustainable and efficient manner. These advancements have not only improved the productivity and profitability of flower farming but have also contributed to the conservation of natural resources and the protection of the environment.